Rust-resistant grouting material and preparation process thereof

By accurately proportioning the main raw materials such as cement, fly ash, silica fume and other admixtures in the grouting material, and adopting a specific stirring process, the problems of poor fluidity and poor water retention in traditional grouting projects are solved, and higher quality stability and durability are achieved.

CN119874282APending Publication Date: 2025-04-25陕西路桥集团有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510011677.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-04
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Traditional grouting projects often face problems such as poor liquidity, poor water retention, large system shrinkage and easy rust of steel bars.

Method used

By providing a rust-resisting grout material, the ratio includes cement, fly ash, silica fume, anti-flash rust agent, expansion agent, water reducing agent, defoaming agent, cellulose ether and gas induction agent, a specific stirring process is used to ensure uniform mixing of the components.

Benefits of technology

The grouting material has better quality stability and fluidity, has a small amount of water secretion, is not easy to segregate and delaminate, has a smooth grouting process, is not easy to block the pipe, and has a small effect on the corrosion of the steel bars. The hardened slurry has high density, full pores, great adhesion to prestressed steel bars, high structural strength and improved durability after solidification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874282A_ABST
    Figure CN119874282A_ABST
Patent Text Reader

Abstract

The invention discloses a rust-resistant grouting material and a preparation process thereof, and relates to the technical field of prestressed concrete. The rust-resistant grouting material is prepared from the following components in parts by weight: 70 to 85 parts of cement, 5 to 15 parts of fly ash, 10 to 20 parts of silica fume, 0.01 to 0.04 part of a flash-rust inhibitor, 0.01 to 0.04 part of an expanding agent, 0.1 to 0.5 part of a water reducing agent, 0.03 to 0.07 part of a de-foaming agent, 0.03 to 0.06 part of cellulose ether and 0.2 to 0.6 part of an air entraining agent. Therefore, by adopting the cement, the fly ash and the silica fume as main raw materials and accurately proportioning the main raw materials with other additives, the prepared slurry is better in quality stability, better in flowability, small in bleeding, not easy to separate and layer, smooth in grouting, not easy to block pipes, not easy to corrode reinforcing steel bars, compact in hardened slurry, full in pore channels, good in durability and good in durability. The cohesive force with prestressed steel bars is large, and after solidification, the structural strength is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of prestressed concrete, and in particular to a rust-resistant grouting material and a preparation process thereof. Background Art

[0002] With the continuous maturity and development of prestressed concrete technology, prestressed concrete structural components have been widely used in infrastructure construction such as construction projects and bridge projects. Prestressed concrete structural components can significantly improve the bearing capacity and durability of the structure by applying stress in advance, and are an indispensable and important part of modern engineering. However, in the construction process of prestressed concrete structural components, especially the post-tensioning prestressing construction link, extremely high requirements are placed on the performance of the grouting material.

[0003] Post-tensioning prestressing construction involves the tensioning and anchoring of prestressed tendons and the subsequent pipe grouting process. As a key step in connecting prestressed tendons and concrete, the quality of pipe grouting directly determines the overall performance and safety of prestressed structural components.

[0004] However, in the actual construction process, pipeline grouting often faces many quality problems, most of which are caused by insufficient performance of grouting materials or compatibility problems between components. Specifically, the poor compatibility of various admixtures in the grouting material and the poor adaptability of cement and water reducer are the main reasons for the quality problems of pipeline grouting. These problems will lead to poor slurry quality stability, insufficient fluidity and poor volume stability. The slurry has a large amount of water exudation and is easy to segregate and stratify, which will not only affect the smoothness of the grouting process, but also increase the risk of steel corrosion. Summary of the invention

[0005] The embodiments of the present application solve the technical problems of poor fluidity, poor water retention, large system shrinkage and easy rust of steel bars commonly existing in traditional grouting projects by providing a rust-resistant grouting material and a preparation process thereof.

[0006] In a first aspect, the present invention provides a rust-proof slurry, which comprises the following components by weight ratio:

[0007] Cement 70-85 parts, fly ash 5-15 parts, silica fume 10-20 parts, anti-flash rust agent 0.01-0.04 parts, expansion agent 0.01-0.04 parts, water reducing agent 0.1-0.5 parts, defoaming agent 0.03-0.07 parts, cellulose ether 0.03-0.06 parts, air entraining agent 0.2-0.6 parts.

[0008] In combination with the first aspect, in a possible implementation, the fly ash is collected after calcining anthracite.

[0009] In combination with the first aspect, in a possible implementation, the silicon ash comes from a by-product generated during the smelting of silicon metal.

[0010] In combination with the first aspect, in a possible implementation, the cement is ordinary Portland cement.

[0011] In combination with the first aspect, in a possible implementation manner, the anti-flash rust agent is an anodic anti-flash rust agent.

[0012] In combination with the first aspect, in a possible implementation manner, the expansion agent is one or more of a UEA expansion agent, a PE expansion agent, and a HEA expansion agent.

[0013] In combination with the first aspect, in a possible implementation, the water reducer is one or more of a naphthalene-based high-efficiency water reducer, an aliphatic high-efficiency water reducer, an amino high-efficiency water reducer, and a polycarboxylic acid high-performance water reducer.

[0014] In combination with the first aspect, in a possible implementation, the defoaming agent is an emulsified silicone oil defoaming agent.

[0015] In combination with the first aspect, in a possible implementation, the cellulose ether is hydroxypropyl methylcellulose.

[0016] In a second aspect, an embodiment of the present application provides a preparation process of a rust-resistant press slurry, including the rust-resistant press slurry described in the first aspect or any possible implementation of the first aspect, the process comprising:

[0017] In a powder mixer, add the following components in proportion: 70-85 parts of cement, 5-15 parts of fly ash, 10-20 parts of silica fume, 0.01-0.04 parts of flash rust preventer, 0.01-0.04 parts of expansion agent, 0.1-0.5 parts of water reducer, 0.03-0.07 parts of defoamer, 0.03-0.06 parts of cellulose ether, and 0.2-0.6 parts of air entraining agent, then start the powder mixer until a uniform mixed powder is obtained;

[0018] Open the valve of the powder mixer and discharge the mixed powder into the storage tank for subsequent use;

[0019] Add an appropriate amount of water into the grouting mixer, and pour in 55%-65% of the mixed powder, adjust the speed of the grouting mixer to 600r / min, stir for 1-2 minutes, add the remaining mixed powder into the grouting mixer again, then adjust the speed of the grouting mixer to 1500r / min, continue stirring for 5 minutes to obtain a uniformly mixed slurry.

[0020] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects:

[0021] The anti-rust grout provided in the embodiment of the present application includes the following components by weight ratio: 70-85 parts of cement, 5-15 parts of fly ash, 10-20 parts of silica ash, 0.01-0.04 parts of anti-flash rust agent, 0.01-0.04 parts of expansion agent, 0.1-0.5 parts of water reducer, 0.03-0.07 parts of defoamer, 0.03-0.06 parts of cellulose ether, and 0.2-0.6 parts of air entraining agent. In this formula, the addition of fly ash can effectively absorb more free water through hydrogen bonds due to its stronger polarity, thereby enhancing water retention. Silica ash can react with cement hydration product Ca(OH)2 to form hydrated calcium silicate gel, which can fill the gaps between cement particles, optimize the interface structure and enhance the bonding force, forming a denser structure, thereby enhancing the strength of the slurry.

[0022] The addition of anti-flash rust agent can closely bond with the steel bar surface to form a passivation layer, effectively preventing electrochemical corrosion of water on metal. The expansion agent can form uniform and dense micropores in an alkaline environment, causing the system to expand slightly, thereby effectively solving the shrinkage problem of the slurry and improving the filling of the slurry.

[0023] The addition of air-entraining agent can significantly improve the concrete's frost resistance, salt resistance, impermeability, sulfate erosion resistance and alkali-aggregate reaction resistance. Water reducer is used to improve the fluidity of the slurry, while defoamer is used to control the gas content of the slurry to improve its compactness. If the defoamer content is too low, the slurry may have a high gas content, thereby reducing its compressive strength. Cellulose ether has water retention properties. By forming hydrogen bonds with water molecules, free water is converted into bound water, thereby improving the water retention of cement slurry. This property is particularly important in the production of grouting materials, which can improve the rheological properties and porous network structure of fresh cement slurry.

[0024] Therefore, the slurry prepared by the present application through precise proportioning of cement, fly ash, silica fume and other main raw materials and other admixtures has better quality stability and fluidity, less water exudation, less segregation and stratification, smooth grouting process, less pipe clogging, and less corrosion to steel bars. The hardened slurry has high density, full pores, and strong bonding with prestressed steel bars. After solidification, the structure has high strength and is less likely to crack for a long time, thereby effectively improving the durability of construction projects, bridge projects, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings required for use in the description of the embodiments of the present application. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 A flow chart of the preparation process of the rust-resistant slurry provided in an embodiment of the present application. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0028] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship indicated by the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc. is based on the orientation or positional relationship shown in the drawings, and is only for the convenience of describing the embodiments of the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. The terms "first", "second", and "third" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance. In addition, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0029] The present application embodiment provides a rust-proof slurry, such as Figure 1 As shown, the rust-proof slurry comprises the following components by weight ratio:

[0030] Cement 70-85 parts, fly ash 5-15 parts, silica fume 10-20 parts, anti-flash rust agent 0.01-0.04 parts, expansion agent 0.01-0.04 parts, water reducing agent 0.1-0.5 parts, defoaming agent 0.03-0.07 parts, cellulose ether 0.03-0.06 parts, air entraining agent 0.2-0.6 parts.

[0031] It should be noted that the secondary hydration of fly ash enhances the compactness of concrete and optimizes the interface structure. In addition, the secondary reaction reduces the amount of calcium hydroxide that is susceptible to corrosion, thereby improving the concrete's impermeability and sulfate corrosion resistance. Silica fume can react with cement hydration product Ca(OH)2 to form hydrated calcium silicate gel, which can fill the gaps between cement particles, optimize the interface structure and enhance the bonding force, forming a denser structure, thereby enhancing the strength of the slurry.

[0032] The addition of anti-flash rust agent can closely bond with the steel bar surface to form a passivation layer, effectively preventing electrochemical corrosion of water on metal. The expansion agent can form uniform and dense micropores in an alkaline environment, causing the system to expand slightly, thereby effectively solving the shrinkage problem of the slurry and improving the filling of the slurry.

[0033] The addition of air-entraining agent can significantly improve the concrete's frost resistance, salt resistance, impermeability, sulfate erosion resistance and alkali-aggregate reaction resistance. Water reducer is used to improve the fluidity of the slurry, while defoamer is used to control the gas content of the slurry to improve its compactness. If the defoamer content is too low, the slurry may have a high gas content, thereby reducing its compressive strength. Cellulose ether has water retention properties. By forming hydrogen bonds with water molecules, free water is converted into bound water, thereby improving the water retention of cement slurry. This property is particularly important in the production of grouting materials, which can improve the rheological properties and porous network structure of fresh cement slurry.

[0034] Therefore, the slurry prepared by the present application through precise proportioning of cement, fly ash, silica fume and other main raw materials and other admixtures has better quality stability and fluidity, less water exudation, less segregation and stratification, smooth grouting process, less pipe clogging, and less corrosion to steel bars. The hardened slurry has high density, full pores, and strong bonding with prestressed steel bars. After solidification, the structure has high strength and is less likely to crack for a long time, thereby effectively improving the durability of construction projects, bridge projects, etc.

[0035] In the embodiment of the present application, fly ash is collected after calcining anthracite. This calcination process can make the particle structure of fly ash more uniform and dense, thereby improving its compressive strength and durability. Through calcination, fly ash, an industrial waste, can be utilized as a resource, which not only saves natural resources but also reduces the negative impact on the environment.

[0036] The fly ash of the present application can effectively absorb more free water through hydrogen bonding due to its stronger polarity, thereby enhancing the water retention of the slurry. This improvement in water retention helps the slurry maintain stable performance during the pouring and hardening process, avoids performance degradation caused by excessive water loss, and thus ensures the quality of the project.

[0037] In the embodiments of the present application, silica fume is derived from the by-products produced when smelting silicon metal. Its resource utilization not only helps to reduce the emission of industrial waste and reduce environmental pollution, but also significantly improves the performance of concrete. The addition of silica fume can significantly improve the compressive, tensile and impact strength of concrete. This is because the gel generated by the reaction of silica fume with cement hydration products can enhance the internal bonding of the material and make the material stronger. At the same time, silica fume also gives concrete excellent corrosion resistance, cavitation resistance and frost resistance, thereby improving the durability of the material and extending the service life of composite materials such as concrete.

[0038] In the present embodiment, the cement used is ordinary Portland cement, which has a specific surface area of ​​340 m 2 / kg or more, and the free calcium oxide content is strictly controlled below 0.8%. Specific surface area is an important indicator for measuring cement fineness, which reflects the surface area of ​​cement particles reacting with water. The larger the specific surface area, the finer the cement particles, and the larger the surface area in contact with water. Therefore, cement with moderate fineness can quickly hydrate at an early stage, release a large amount of heat, accelerate the formation of concrete structure, and thus exert its strength performance faster. Controlling the free calcium oxide content below 0.8% can ensure that the cement remains stable during the hardening process and avoid problems such as volume expansion and cracking.

[0039] In the embodiment of the present application, the anti-flash rust agent is an anodic anti-flash rust agent.

[0040] Anodic flash rust inhibitors work mainly by inhibiting the anode reaction of the corrosion cell. Most of these compounds are strong base and weak acid salts, such as phosphates, which can hydrolyze in water to form hydroxide ions and form a passivating oxide layer on the metal surface, effectively preventing oxygen and water from corroding the metal surface.

[0041] Meanwhile, the embodiments of the present application are not limited to the anodic anti-flash rust agent, and may also be cathodic anti-flash rust agents and mixed anti-flash rust agents.

[0042] In the embodiments of the present application, the expansion agent is one or more of a UEA expansion agent, a PE expansion agent, and a HEA expansion agent.

[0043] It should be noted that different expansion agents may produce a synergistic effect, further enhancing the concrete's resistance to cracking, anti-seepage and durability.

[0044] In the embodiment of the present application, the water reducer is one or more of naphthalene-based high-efficiency water reducer, aliphatic high-efficiency water reducer, amino high-efficiency water reducer, and polycarboxylic acid high-performance water reducer. When one or more of these water reducers are used in concrete, significant technical effects can be brought about, including improving the fluidity of concrete, reducing the amount of cement, enhancing the strength of concrete, improving the workability and durability of concrete, etc. These achievements help to optimize the performance of concrete and meet various engineering needs.

[0045] In the embodiment of the present application, the defoaming agent is an emulsified silicone oil defoaming agent. Emulsified silicone oil defoaming agents have excellent defoaming and anti-foaming properties. They can be quickly dispersed in the foam system, and by reducing the surface tension, they effectively destroy the stability of the foam and make the foam disappear quickly. At the same time, they can also inhibit the regeneration of foam for a long time, thereby ensuring the smooth progress of the production process.

[0046] In the examples of the present application, the cellulose ether is hydroxypropyl methylcellulose. Hydroxypropyl methylcellulose has excellent water retention properties and can form a wetting film in cement mortar or gypsum-based materials, allowing the moisture in the substrate to be gradually released over a long period of time.

[0047] The present application provides a process for preparing a rust-resistant press slurry, including the above-mentioned rust-resistant press slurry, and the process includes the following steps S1-S3:

[0048] S1: In a powder mixer, add the following components in proportion: 70-85 parts of cement, 5-15 parts of fly ash, 10-20 parts of silica fume, 0.01-0.04 parts of flash rust preventer, 0.01-0.04 parts of expansion agent, 0.1-0.5 parts of water reducer, 0.03-0.07 parts of defoamer, 0.03-0.06 parts of cellulose ether, and 0.2-0.6 parts of air entraining agent, then start the powder mixer until a uniform mixed powder is obtained;

[0049] S2: Open the valve of the powder mixer and discharge the mixed powder into the storage tank for subsequent use;

[0050] S3: Add an appropriate amount of water into the grouting material mixer, and pour in 55%-65% of the mixed powder, adjust the speed of the grouting material mixer to 600r / min, stir for 1-2 minutes, add the remaining mixed powder into the grouting material mixer again, then adjust the speed of the grouting material mixer to 1500r / min, continue stirring for 5 minutes, and obtain a uniformly mixed slurry.

[0051] Embodiment 1:

[0052] In a powder mixer, add the following components in the following proportions: 75 parts of cement, 5 parts of fly ash, 10 parts of silica fume, 0.01 parts of flash rust inhibitor, 0.01 parts of expansion agent, 0.1 parts of water reducer, 0.05 parts of defoaming agent, 0.03 parts of cellulose ether and 0.2 parts of air entraining agent. Start the powder mixer and first stir at a low speed of 25 r / min for 3 minutes. Then, adjust the speed to 50 r / min and continue stirring for 30 minutes until a completely uniform mixed powder is obtained.

[0053] It should be noted that the initial stage of low-speed stirring is crucial for the initial mixing of the component materials, especially trace additives such as flash rust inhibitors, expansion agents, and water reducers. Under low-speed stirring, these additives can be more evenly dispersed in the main material. This avoids the problem of strong shear force generated at the beginning of high-speed stirring, which may cause additives to agglomerate or unevenly distribute. At the same time, by stirring at low speed first and then high speed, operators can better control the state and mixing effect of the materials. During the low-speed stirring stage, they can closely observe the mixing of the materials and adjust the stirring time or speed according to actual needs to ensure the smooth progress of subsequent high-speed stirring. This flexibility not only helps to optimize process parameters, but also significantly improves product quality.

[0054] Open the valve of the powder mixer and discharge the mixed powder into the storage tank for subsequent use.

[0055] Add an appropriate amount of water into the grouting mixer, and pour in 60% of the mixed powder, adjust the speed of the grouting mixer to 600r / min, stir for 1-2 minutes, add the remaining mixed powder into the grouting mixer again, then adjust the speed of the grouting mixer to 1500r / min, continue stirring for 5 minutes to obtain a uniformly mixed slurry.

[0056] Grind the plain round steel bar until there is no rust and ensure that it is 100mm long. Then, evenly apply epoxy resin to the area 30mm inward from both ends of the plain round steel bar, and then put on the heat shrink tube for protection. Finally, connect a 60mm long wire to the exposed end of the plain round steel bar. Put the treated plain round steel bar into the production mold and evenly pour the prepared slurry on it. After the slurry solidifies for 24 hours, demould it to obtain the test piece.

[0057] After demoulding, the specimens were placed in a room with a room temperature of 21°C and a humidity of 65% for 24 hours. After that, the specimens were immersed in a 3.5% saturated sodium chloride solution for 24 hours. This process constitutes a dry-wet cycle. After one cycle, the potential and resistance of the steel bars inside the slurry were tested, and the changes in potential and resistance were observed to determine whether the steel bars were corroded. Once the steel bars were judged to be corroded, the dry-wet cycle was stopped. Finally, the slurry was cut and the exposed steel bar surface was observed for signs of corrosion.

[0058] Embodiment 2:

[0059] In a powder mixer, add the following components in the following proportions: 80 parts of cement, 8 parts of fly ash, 13 parts of silica fume, 0.02 parts of flash rust inhibitor, 0.02 parts of expansion agent, 0.2 parts of water reducer, 0.06 parts of defoaming agent, 0.04 parts of cellulose ether and 0.4 parts of air entraining agent. Start the powder mixer and first stir at a low speed of 25 r / min for 3 minutes. Then, adjust the speed to 50 r / min and continue stirring for 30 minutes until a completely uniform mixed powder is obtained.

[0060] Open the valve of the powder mixer and discharge the mixed powder into the storage tank for subsequent use.

[0061] Add an appropriate amount of water into the grouting mixer, and pour in 60% of the mixed powder, adjust the speed of the grouting mixer to 600r / min, stir for 1-2 minutes, add the remaining mixed powder into the grouting mixer again, then adjust the speed of the grouting mixer to 1500r / min, continue stirring for 5 minutes to obtain a uniformly mixed slurry.

[0062] Grind the plain round steel bar until there is no rust and ensure that it is 100mm long. Then, evenly apply epoxy resin to the area 30mm inward from both ends of the plain round steel bar, and then put on the heat shrink tube for protection. Finally, connect a 60mm long wire to the exposed end of the plain round steel bar. Put the treated plain round steel bar into the production mold and evenly pour the prepared slurry on it. After the slurry solidifies for 24 hours, demould it to obtain the test piece.

[0063] After demoulding, the specimens were placed in a room with a room temperature of 21°C and a humidity of 65% for 24 hours. After that, the specimens were immersed in a 3.5% saturated sodium chloride solution for 24 hours. This process constitutes a dry-wet cycle. After one cycle, the potential and resistance of the steel bars inside the slurry were tested, and the changes in potential and resistance were observed to determine whether the steel bars were corroded. Once the steel bars were judged to be corroded, the dry-wet cycle was stopped. Finally, the slurry was cut and the exposed steel bar surface was observed for signs of corrosion.

[0064] Embodiment 3:

[0065] In a powder mixer, add the following components in the following proportions: 85 parts of cement, 10 parts of fly ash, 15 parts of silica fume, 0.03 parts of flash rust inhibitor, 0.02 parts of expansion agent, 0.3 parts of water reducer, 0.07 parts of defoaming agent, 0.05 parts of cellulose ether, and 0.6 parts of air entraining agent. Start the powder mixer and first stir at a low speed of 25 r / min for 3 minutes. Then, adjust the speed to 50 r / min and continue stirring for 30 minutes until a completely uniform mixed powder is obtained.

[0066] Open the valve of the powder mixer and discharge the mixed powder into the storage tank for subsequent use.

[0067] Add an appropriate amount of water into the grouting mixer, and pour in 60% of the mixed powder, adjust the speed of the grouting mixer to 600r / min, stir for 1-2 minutes, add the remaining mixed powder into the grouting mixer again, then adjust the speed of the grouting mixer to 1500r / min, continue stirring for 5 minutes to obtain a uniformly mixed slurry.

[0068] Grind the plain round steel bar until there is no rust and ensure that it is 100mm long. Then, evenly apply epoxy resin to the area 30mm inward from both ends of the plain round steel bar, and then put on the heat shrink tube for protection. Finally, connect a 60mm long wire to the exposed end of the plain round steel bar. Put the treated plain round steel bar into the production mold and evenly pour the prepared slurry on it. After the slurry solidifies for 24 hours, demould it to obtain the test piece.

[0069] After demoulding, the specimens were placed in a room with a room temperature of 21°C and a humidity of 65% for 24 hours. After that, the specimens were immersed in a 3.5% saturated sodium chloride solution for 24 hours. This process constitutes a dry-wet cycle. After one cycle, the potential and resistance of the steel bars inside the slurry were tested, and the changes in potential and resistance were observed to determine whether the steel bars were corroded. Once the steel bars were judged to be corroded, the dry-wet cycle was stopped. Finally, the slurry was cut and the exposed steel bar surface was observed for signs of corrosion.

[0070] The cement in the above-mentioned embodiments 1-3 is ordinary silicate cement, with a specific surface area of ​​more than 340m2 / kg and a free calcium oxide content of no more than 0.8%. Fly ash is collected from anthracite after calcination, silica ash comes from the by-products produced when smelting silicon metal, the flash rust preventer includes amino, carboxyl, fluoroalkyl and phosphate functional groups, and mainly uses an anode type flash rust preventer, the expansion agent is one or more of UEA expansion agent, PE expansion agent, and HEA expansion agent, the water reducer is one or more of naphthalene-based high-efficiency water reducer, aliphatic high-efficiency water reducer, amino high-efficiency water reducer, and polycarboxylic acid high-performance water reducer, the defoamer is an emulsified silicone oil defoamer, and the cellulose ether is hydroxypropyl methylcellulose.

[0071] Comparative Example 1:

[0072] In the powder reactor, add the following components in the following proportions: 85 parts of cement, 10 parts of fly ash, 15 parts of silica fume, 0.02 parts of expansion agent, 0.3 parts of water reducer, 0.07 parts of defoamer, 0.05 parts of cellulose ether and 0.4 parts of air entraining agent. Start the powder agitator and first stir at a low speed of 25 r / min for 3 minutes. Then, adjust the speed to 50 r / min and continue stirring for 30 minutes until a completely mixed powder is obtained.

[0073] Open the valve of the powder mixer and discharge the mixed powder into the storage tank for subsequent use.

[0074] Add an appropriate amount of water into the grouting mixer, and pour in 60% of the mixed powder, adjust the speed of the grouting mixer to 600r / min, stir for 1-2 minutes, add the remaining mixed powder into the grouting mixer again, then adjust the speed of the grouting mixer to 1500r / min, continue stirring for 5 minutes to obtain a uniformly mixed slurry.

[0075] Grind the plain round steel bar until there is no rust and ensure that it is 100mm long. Then, evenly apply epoxy resin to the area 30mm inward from both ends of the plain round steel bar, and then put on the heat shrink tube for protection. Finally, connect a 60mm long wire to the exposed end of the plain round steel bar. Put the treated plain round steel bar into the production mold and evenly pour the prepared slurry on it. After the slurry solidifies for 24 hours, demould it to obtain the test piece.

[0076] After demoulding, the specimens were placed in a room with a room temperature of 21°C and a humidity of 65% for 24 hours. After that, the specimens were immersed in a 3.5% saturated sodium chloride solution for 24 hours. This process constitutes a dry-wet cycle. After one cycle, the potential and resistance of the steel bars inside the slurry were tested, and the changes in potential and resistance were observed to determine whether the steel bars were corroded. Once the steel bars were judged to be corroded, the dry-wet cycle was stopped. Finally, the slurry was cut and the exposed steel bar surface was observed for signs of corrosion.

[0077] Comparative Example 2:

[0078] In the powder reactor, add the following components in the following proportions: 75 parts of cement, 5 parts of fly ash, 10 parts of silica fume, 0.01 parts of expansion agent, 0.1 parts of water reducer, 0.05 parts of defoaming agent, and 0.4 parts of air entraining agent. Start the powder agitator and first stir at a low speed of 25 r / min for 3 minutes. Then, adjust the speed to 50 r / min and continue stirring for 30 minutes until a completely mixed powder is obtained.

[0079] Open the valve of the powder mixer and discharge the mixed powder into the storage tank for subsequent use.

[0080] Add an appropriate amount of water into the grouting mixer, and pour in 60% of the mixed powder, adjust the speed of the grouting mixer to 600r / min, stir for 1-2 minutes, add the remaining mixed powder into the grouting mixer again, then adjust the speed of the grouting mixer to 1500r / min, continue stirring for 5 minutes to obtain a uniformly mixed slurry.

[0081] Grind the plain round steel bar until there is no rust and ensure that it is 100mm long. Then, evenly apply epoxy resin to the area 30mm inward from both ends of the plain round steel bar, and then put on the heat shrink tube for protection. Finally, connect a 60mm long wire to the exposed end of the plain round steel bar. Put the treated plain round steel bar into the production mold and evenly pour the prepared slurry on it. After the slurry solidifies for 24 hours, demould it to obtain the test piece.

[0082] After demoulding, the specimens were placed in a room with a room temperature of 21°C and a humidity of 65% for 24 hours. After that, the specimens were immersed in a 3.5% saturated sodium chloride solution for 24 hours. This process constitutes a dry-wet cycle. After one cycle, the potential and resistance of the steel bars inside the slurry were tested, and the changes in potential and resistance were observed to determine whether the steel bars were corroded. Once the steel bars were judged to be corroded, the dry-wet cycle was stopped. Finally, the slurry was cut and the exposed steel bar surface was observed for signs of corrosion.

[0083] The present invention tests Examples 1-3 and Comparative Examples 1-2 according to TB / T3192-2008 "Technical Conditions for Pipe Grouting of Railway Post-Tensioned Prestressed Concrete Beams", and the test data are shown in Table 1.

[0084] Table 1 is the test data of Examples 1-3 and Comparative Examples 1-2

[0085]

[0086] The above results show that in the performance test of Example 1-3 and Comparative Example 1-2, the steel bars in Example 1-3 using the raw materials of the present application and adding the anti-flash rust agent did not rust, while the steel bars in Comparative Example 1-2 without adding the anti-flash rust agent did rust. In addition, the slurry fluidity time of Example 1-3 with the addition of the anti-flash rust agent is shorter than that of Comparative Example 1-2. The fluidity of Example 1-3 and Comparative Example 1 is lower than that of Comparative Example 2 after standing for 60 minutes, and sinking to the bottom occurs, indicating that cellulose ether has water retention for grouting. In general, the slurry prepared using the raw materials of the present application has good quality stability, small slurry exudation, and is not easy to separate and stratify. The grouting is smooth and not easy to block the pipe. The hardened slurry has high density, full pores, and strong bonding with prestressed steel bars. After solidification, the structural strength is high, and no cracks will occur after a long time, thereby effectively improving the durability of construction projects, bridge projects, etc.

[0087] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other. Each embodiment focuses on the differences from other embodiments.

[0088] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A rust-proof slurry, characterized in that: The components by weight are as follows: Cement 70-85 parts, fly ash 5-15 parts, silica fume 10-20 parts, anti-flash rust agent 0.01-0.04 parts, expansion agent 0.01-0.04 parts, water reducing agent 0.1-0.5 parts, defoaming agent 0.03-0.07 parts, cellulose ether 0.03-0.06 parts, air entraining agent 0.2-0.6 parts.

2. The anti-rust slurry according to claim 1, characterized in that: The fly ash is collected after calcining anthracite.

3. The anti-rust slurry according to claim 1, characterized in that: The silicon ash is a by-product produced when smelting silicon metal.

4. The anti-rust slurry according to claim 1, characterized in that: The cement is ordinary Portland cement.

5. The anti-rust slurry according to claim 1, characterized in that: The anti-flash rust agent is an anodic anti-flash rust agent.

6. The anti-rust slurry according to claim 1, characterized in that: The expansion agent is one or more of a UEA expansion agent, a PE expansion agent, and a HEA expansion agent.

7. The anti-rust slurry according to claim 1, characterized in that: The water reducer is one or more of naphthalene-based high-efficiency water reducer, aliphatic high-efficiency water reducer, amino high-efficiency water reducer, and polycarboxylic acid high-performance water reducer.

8. The anti-rust slurry according to claim 1, characterized in that: The defoamer is an emulsified silicone oil defoamer.

9. The anti-rust slurry according to claim 1, characterized in that: The cellulose ether is hydroxypropyl methylcellulose.

10. A process for preparing a rust-resistant press slurry, characterized in that: The rust-proof slurry according to any one of claims 1 to 9, wherein the process comprises: In a powder mixer, add the following components in proportion: 70-85 parts of cement, 5-15 parts of fly ash, 10-20 parts of silica fume, 0.01-0.04 parts of flash rust preventer, 0.01-0.04 parts of expansion agent, 0.1-0.5 parts of water reducer, 0.03-0.07 parts of defoamer, 0.03-0.06 parts of cellulose ether, and 0.2-0.6 parts of air entraining agent, then start the powder mixer until a uniform mixed powder is obtained; Open the valve of the powder mixer and discharge the mixed powder into the storage tank for subsequent use; Add an appropriate amount of water into the grouting mixer, and pour in 55%-65% of the mixed powder, adjust the speed of the grouting mixer to 600r / min, stir for 1-2 minutes, add the remaining mixed powder into the grouting mixer again, then adjust the speed of the grouting mixer to 1500r / min, continue stirring for 5 minutes to obtain a uniformly mixed slurry.